Discernment from the youth standpoint upon young leaderships in politics: A case study in Malaysia - Nathen, Bryan; Shekh Alsagoff, Syed Agil; Abdul Rahman, Saiful Nujaimi; Ahmad Suhaimi, Siti Shazwani; Nazuri, Nur Shuhamin (Human Resource Management Academic Research Society, 2021)
In the earlier days of politics, youths were apathetic in the field of politics as the culture of politics was more suited to the older generation. This is because the older generation had more opportunities to cast partisan votes and developed stronger affiliations to the party for which they voted. However, with the ability to access information and engage online for everyone, this heterogeneous culture has given Malaysian youths a new and tangible existence in the scene of politics. Therefore, the purposes of this study is to explore the issues faced by youths in politics, how can aspiring politicians communicate effectively with youths today and to understand how does political communication work in youth circles. The study interviewed fifteen respondents, which all of them were university students between the ages of 18 and 35. The data collection strategy was an in-depth interview followed by a semi-structured interview protocol. Through the thematic analysis, this study found that there are still barriers surrounding politics, which are age, experience, and general perception between old and new politicians, including education, which seems to be a recurring topic. Furthermore, this research also spotted out that females do not have a significant share of voice in politics. This has concluded that the youth political environment remains an undeveloped area in Malaysia.